Transform Coding in the VVC Standard - Zhao, Xin; Kim, Seung-Hwan; Zhao, Yin; Egilmez, Hilmi E.; Koo, Moonmo; Liu, Shan; Lainema, Jani; Karczewicz, Marta (IEEE transactions on circuits and systems for video technology, 2021)
In the past decade, the development of transform coding techniques has achieved significant progress and several advanced transform tools have been adopted in the new generation Versatile Video Coding (VVC) standard. In this paper, a brief history of transform coding development during VVC standardization is presented, and the transform coding tools in the VVC standard are described in detail together with their initial design, incremental improvements and implementation aspects. To improve coding efficiency, four new transform coding techniques are introduced in VVC, which are namely Multiple Transform Selection (MTS), Low-Frequency Non-separable Secondary Transform (LFNST) and Sub-Block Transform (SBT), as well as a large (64-point) type-2 DCT. The experimental results on VVC reference software (VTM-9.0) show that average 4.5% and 3.6% overall coding gain can be achieved by the VVC transform coding tools for All Intra and Random Access configurations, respectively.